Caso de estudio: plan comercial y de marketing para potenciar las exportaciones de la empresa Artest S.A.C. - Villanueva Tocas, Carolina Ines (2020)
Artest SAC is a Peruvian company, founded in 2011 by Itala Testino, a renowned designer in the fashion world, who has been working in the haute couture sector with luxurious alpaca designs and garments with imported fabrics for the High market End. However, it lacks innovation and knowledge of the new tools for sales, advertising, among others. This has caused various problems related to costs, sales, advertising, distribution, etc. to occur throughout its trajectory. Artest S.A.C. It is a company that started its commercialization activities in 2011, specializing in the manufacture of high fashion garments in flat fabric with alpaca fiber. Since its creation, the company has been characterized by bringing together all the trends worldwide to make unique and exclusive designs in each collection, thus giving value to each of its garments by making only two or three of the same models, thus prioritizing exclusivity accompanied by a high-quality hand finish. Since its creation, the company has participated in different fairs worldwide to be at the forefront of new trends and thus incorporate them into their garments before others. This is how in 2011, the company began its foreign trade activities, reaching the US market first. Currently, the products, with the ITALA TESTINO brand, are located in the United States, Chile, Canada, in addition to this, the company is in negotiations to enter the Chinese and European markets (Netherlands and Spain). As will be seen in later paragraphs, exports have gained strength this year thanks to various efforts in the area of marketing and sales. Participations in national and international fairs and the internationalization support program (MYP) have generated a positive impact on the company, thus increasing its competitiveness in different fields. The creation of a web page, brand registration, e-commerce, are some of the achievements that were achieved through the joint effort of the team. The surname TESTINO has given the company a plus, which has helped position it in the international market thanks to its renowned cousin Mario Testino, a Peruvian professional photographer. However, the company's growth is mainly due to efforts in the area of sales and marketing, according to the plan developed in this work, for which several professionals specialized in costs, sales, advertising, etc. were hired. The foreign trade xi advisor has been instrumental in the development of small work plans that together have driven the growth of the company, not only economically. It is important to emphasize that a plan prepared according to the objectives set out clearly, will undoubtedly generate success for a company.